Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan UMKM Kuliner di Kecamatan Semampir Kota Surabaya - Lukita, Safira Aprilia; Sitohang, Arga Christian (Widya Balina, 2024)
The purpose of this study was to analyse the effect of business capital and labour on the income of Culinary MSMEs in Semampir District, Surabaya City. This research method uses descriptive quantitative methods, data collection techniques in the form of questionnaires or questionnaires with a sampling of 50 respondents. The results showed that business capital and labour had a positive effect on the income of Culinary MSMEs in Semampir District, Surabaya City. It is hoped that this information can provide benefits or input to Culinary MSME players in making decisions related to business capital and labour in order to increase the income of Culinary MSMEs in Semampir District, Surabaya City.